When and Why People Engage in Different Forms of Proactive Behavior: Interactive Effects of Self-construals and Work Characteristics - Wu, Chia-Huei; Parker, Sharon K.; Wu, Long-Zeng; Lee, Cynthia (Academy of Management Journal, 2018)
When and why do people engage in different forms of proactive behavior at work? We propose that as a result of a process of trait activation, employees with different types of self-construal engage in distinct forms of proactive behavior if they work in environments consistent with their self-construals. In an experimental Study 1 (n = 61), we examined the effect of self-construals on proactivity and found that people primed with interdependent self-construals engaged in more work unit–oriented proactive behavior when job interdependence was also manipulated. Priming independent self-construals did not enhance career-oriented proactive behavior, even when we manipulated job autonomy. In a field Study 2 (n = 205), we found that employees with interdependent self-construals working in jobs with high interdependence reported higher work unit commitment and higher work unit–oriented proactive behavior compared to employees in low interdependent jobs. Employees with independent self-construals working in jobs with high autonomy also exhibited stronger career commitment and more career-oriented proactive behavior than did those in jobs with low autonomy. This research offers a theoretical framework to explain how dispositional and situational factors interactively shape people’s engagement in different forms of proactive behavior.